Field evaluation of Low Energy Water Application device and Mini-sprinkler Pressurized Irrigation Technologies in Wheat crop - KUMARI, ARTI; GUPTA, S.P.; UPADHYAYA, ASHUTOSH; KUMAR, AJAY; AHMED, AKRAM; SINGH, ATUL KUMAR (Journal of Soil and Water Conservation, 2023)
A field experiment was carried out for evaluating the field performance of Low Energy Water Application (LEWA) (0.4 to 0.6 kg/cm2) and Mini Sprinkler (1.2 to 1.4 kg/cm2) in Wheat crop at water management plot of Dr. Rajendra Prasad Central Agricultural University, Pusa, Samastipur, Bihar. Results revealed that in both the cases i.e. LEWA and mini-sprinkler, the discharge and wetted diameter increased with increase in operating pressure. LEWA has capability to produce more discharge at very low pressure in comparison to mini sprinkler and due to shifting adjustment; it has capability to irrigate more land in lesser time. However, the net amount of water applied through mini-sprinkler and LEWA irrigation were 360 mm and 300 mm, respectively. Total 16.67% of water was saved in LEWA as compared to minisprinkler. Total yield of Wheat was 3547 and 3928 kg/ha for mini-sprinkler and LEWA irrigations, respectively. Overall, results revealed that LEWA has capability to save irrigation time (18.42 per cent), per hour fuel saving (19.15 per cent), money (27.48 per cent in operations) in addition to 16.67 per cent water saving by reducing frequency of irrigation interval. Therefore, it was concluded that LEWA is one of the most promising low-cost water saving technology for small and marginal farmers.